Beads of agency: Bemba women"s imbusa and indigenous marital communication - Kaunda, Mutale M. (HTS teologiese studies, 2023)
In this article the author argues that indigenous Bemba women of Zambia used their culture of symbolic communication for marital sex agency. African women are often portrayed as not having agency and negotiating power when it comes to sex whether in marital or casual relationships. However, through imbusa teachings, Bemba women of Zambia had the negotiating power and agency over their sexual desires using indigenous beads as a marital communication tool before Christianity, interaction with various cultures, and colonial activity infiltrated the institution of imbusa. Missionaries were consistently and insistently invading the space of imbusa claiming the need to be made aware of what was being taught. Missionaries claimed that they wanted to prepare a manual for new arriving priests so that they would include Christianity to the teachings in order to teach the Bemba women Christian ways of marriage. As a result, much of the indigenous imbusa teaching was portrayed as demonic and Bemba women needed to disregard them in order to be Christian married women. Using symbolic interactionism, this article will demonstrate the teachings of imbusa that gave Bemba women agency to express and negotiate their sexual desires in marriage. Bemba women had a ritual of hanging beads on the wall or placing them on the bed at certain times in their marriage. For instance, when they were menstruating, they hung red beads which was to communicate that they were not available for sexual relations.Contribution: This article contributes to the African indigenous cultural understandings and positions held by indigenous women prior to their interactions with diverse cultures and religious views. Contemporary indigenous women can leverage some positive feminist approaches from within the culture.